2011
DOI: 10.1007/s10393-011-0711-0
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Sustainability into Community-Based Healthcare Practice

Abstract: There is now irrefutable evidence that climate change and increasing environmental degradation negatively affect population health. Healthcare plays an important role in addressing these emerging environmental challenges, considering its core aim is to protect and promote health. Preliminary research in Victoria, Australia, suggests that healthcare practitioners are endeavouring to factor in environmental concerns into their practice. Health promotion, an integral part of the healthcare system, is considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 15 publications
2
39
0
1
Order By: Relevance
“…Connell et al concluded that "the overarching goals of health and sustainability facilitate collaboration among disciplines" but "that differences arise from how each approach operationalizes systems as variables and indicators" and, therefore, that "the concepts of health and sustainability can be used to study ecosystems and livelihoods at various scales" [74]. Patrick et al outline that the individual competencies inherent to health promotion that are useful for engaging with health and sustainability are "individual behavior, organization and social change, partnership development, advocacy for policy and legislative change, and community engagement" [75]. In their study they performed interviews that revealed the sentiment that the "absence of a comprehensive framework to guide action on health and sustainability" is a main barrier for "incorporating sustainability into healthcare practice" [75].…”
Section: Sustainable Usementioning
confidence: 99%
See 4 more Smart Citations
“…Connell et al concluded that "the overarching goals of health and sustainability facilitate collaboration among disciplines" but "that differences arise from how each approach operationalizes systems as variables and indicators" and, therefore, that "the concepts of health and sustainability can be used to study ecosystems and livelihoods at various scales" [74]. Patrick et al outline that the individual competencies inherent to health promotion that are useful for engaging with health and sustainability are "individual behavior, organization and social change, partnership development, advocacy for policy and legislative change, and community engagement" [75]. In their study they performed interviews that revealed the sentiment that the "absence of a comprehensive framework to guide action on health and sustainability" is a main barrier for "incorporating sustainability into healthcare practice" [75].…”
Section: Sustainable Usementioning
confidence: 99%
“…Patrick et al outline that the individual competencies inherent to health promotion that are useful for engaging with health and sustainability are "individual behavior, organization and social change, partnership development, advocacy for policy and legislative change, and community engagement" [75]. In their study they performed interviews that revealed the sentiment that the "absence of a comprehensive framework to guide action on health and sustainability" is a main barrier for "incorporating sustainability into healthcare practice" [75]. The interviews revealed further that the local agenda 21, healthy cities, Ottawa Charter for Health Promotion, environments for health, the Climate Change Adaptation: a Framework for Action, and the Social Model of Health were identified as facilitators to the "congruence between health and sustainability goals" [75].…”
Section: Sustainable Usementioning
confidence: 99%
See 3 more Smart Citations